2014
DOI: 10.1002/anie.201310735
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Route to Human Insulin Using Isoacyl Peptides

Abstract: The chemical synthesis of insulin has been a longstanding challenge, mainly because of the notorious hydrophobicity of the A chain and the complicated topology of this 51-mer peptide hormone consisting of two chains and three disulfide bonds. Reported herein is a new synthetic route utilizing the isoacyl peptide approach to address the hydrophobicity problems. The incorporation of isoacyl dipeptide segments into both A and B chains greatly improved their preparation and purification, and the RP-HPLC recovery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 32 publications
1
62
0
6
Order By: Relevance
“…Attempts to ameliorate the synthetic routes to human insulin led Liu et al [52] to apply the isoacylconcept, which improved the synthesis of various difficult sequences. Attempts to ameliorate the synthetic routes to human insulin led Liu et al [52] to apply the isoacylconcept, which improved the synthesis of various difficult sequences.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Attempts to ameliorate the synthetic routes to human insulin led Liu et al [52] to apply the isoacylconcept, which improved the synthesis of various difficult sequences. Attempts to ameliorate the synthetic routes to human insulin led Liu et al [52] to apply the isoacylconcept, which improved the synthesis of various difficult sequences.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In 2014, Liu et al. reported that the introduction of isoacyl motifs to the insulin A‐chain could drastically improve its solubility . The same effect was observed for the insulin B‐chain (Scheme A).…”
Section: Application Of Isoacyl Structural Motifs In Synthetic Peptidmentioning
confidence: 81%
“…The synthesis of human INSL‐6 A‐chain 2 (Scheme ) consisting of a pre‐formed CysA6‐CysA11 disulfide bond followed a procedure similar to that previously described for the preparation of the insulin A‐chain, for which CysA6‐ tert ‐butylthiol (S t Bu), CysA7‐Acm, CysA11‐ p ‐methoxytrityl (Mmt), and CysA20‐trityl (Trt) were incorporated during SPPS . The initial solid‐phase assembly of 2 resulted in poor synthetic quality, primarily due to the deletions of the TyrA2 and CysA11 residues (Figure S2 a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To form the CysA7‐CysB13 disulfide, the A–B heterodimer 4 was treated with 25 equivalents I 2 in aqueous acetic acid . (Scheme ).…”
Section: Resultsmentioning
confidence: 99%